2022
DOI: 10.1111/jasp.12915
|View full text |Cite
|
Sign up to set email alerts
|

Goal motives and mental contrasting with implementation intentions facilitate strategic goal persistence and disengagement

Abstract: In three experiments, we examine the role of motives underlying goal pursuit and the metacognitive strategy of mental contrasting with implementation intentions (MCII) to predict the strategic use of self-regulation responses (persistence, disengagement, and reengagement) when faced with attainable, unattainable, or multiple goals. We trained half of the participants to use MCII and treated the rest as control. Experiment 1 (N = 261) underscored the role of autonomous motivation in nurturing adaptive cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…The results pertaining to the alternative models indicated that correlation coefficients were stronger when participants pursued goals in lab-based experiments (compared to life, education, sports, work, social, relationships, and religion goals), and in diary studies (compared to cross-sectional, prospective, and experimental). However, the significant differences observed in the moderation analyses are not interpretable (Higgins et al, 2022), as there was only one study that used lab experiment task goals (Riddell et al, 2022) and only two studies that incorporated a diary design (Milyavskaya & Inzlicht, 2013;Tadić et al, 2013). On the one hand, these findings suggest that meta-analytic effects potentially generalize well across the factors we included as covariates within the analysis.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The results pertaining to the alternative models indicated that correlation coefficients were stronger when participants pursued goals in lab-based experiments (compared to life, education, sports, work, social, relationships, and religion goals), and in diary studies (compared to cross-sectional, prospective, and experimental). However, the significant differences observed in the moderation analyses are not interpretable (Higgins et al, 2022), as there was only one study that used lab experiment task goals (Riddell et al, 2022) and only two studies that incorporated a diary design (Milyavskaya & Inzlicht, 2013;Tadić et al, 2013). On the one hand, these findings suggest that meta-analytic effects potentially generalize well across the factors we included as covariates within the analysis.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, timely disengagement from an unattainable goal and reengagement with a viable alternative might prevent a decline in psychological well-being and support adaptive goal striving (Barlow et al, 2020;Wrosch et al, 2003;Wrosch & Scheier, 2020). Previous research has shown that autonomous goal motives are negatively related to goal disengagement when faced with unattainable goals , but positively related to goal reengagement (Riddell et al, 2022). Clearly, there is still much to be uncovered about how motives contribute to the reassessment of unattainable goals and reengagement with alternative pursuits (e.g., see Ntoumanis & Sedikides, 2018).…”
Section: Future Research Directionsmentioning
confidence: 97%
See 2 more Smart Citations
“…Ntoumanis and Sedikides (2018) proposed that interactions between MCII and goal motives could influence self-regulatory responses to goals. For individuals with controlled motivation, MCII should encourage effort toward attainable goals and accommodative coping in the face of adversity, both of which would otherwise be diminished under controlled motivation (Riddell et al, 2022). Given that autonomous motivation already encourages commitment and persistence, autonomously motivated goals that are attainable should benefit less from MCII (Ntoumanis, Healy, Sedikides, Duda, et al, 2014).…”
Section: The Role Of Motives In Self-regulatory Copingmentioning
confidence: 99%